2017
DOI: 10.7759/cureus.1667
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Acrodermatitis Enteropathica: A Case Study

Abstract: We present a case of severe acquired acrodermatitis enteropathica in a vegan adult female with multiple underlying comorbidities. Acquired acrodermatitis enteropathica or zinc-deficiency dermatitis is the most common diagnosis than many practitioners realize with up to 10% of the patients in developed nations with the risk of zinc deficiency. The condition can be difficult to diagnose due to many similarly-presenting conditions. Furthermore, comorbid conditions in the patients can serve as confounders to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…In our review, we identified just three similar cases. One group described acquired AE in a teenager with anorexia and zinc deficiency 7. Another reported acquired AE in a vegan patient with pancreatic insufficiency presenting with a full body rash 8.…”
Section: Discussionmentioning
confidence: 99%
“…In our review, we identified just three similar cases. One group described acquired AE in a teenager with anorexia and zinc deficiency 7. Another reported acquired AE in a vegan patient with pancreatic insufficiency presenting with a full body rash 8.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] It has also been reported that severe and/or chronic effects of zinc deficiency such as mental status changes or depression treated with zinc supplementation showed significant efficacy. 2 Reports indicate that even inconsistent zinc supplementation can lead to recurrent skin manifestations potentially resulting in severe skin erosions. The importance of high-dose lifelong supplementation is therefore important to discuss with parents when infants are first diagnosed with acrodermatitis enteropathica to prevent flares or further complications.…”
Section: Miscellaneous Causesmentioning
confidence: 99%
“…Dietary zinc is absorbed in the duodenum and jejunum of the small intestine through a specific zinc transporter, ZIP4. 1 , 2 It is then released into the bloodstream via other zinc transporters. In the human body, skin is the third most zinc abundant tissue following skeletal muscle and bone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a 17.3% risk for hypozincemia worldwide; in developed nations there is an estimated 3% to 10% occurrence rate. 2 Acrodermatitis enteropathica can be classified as either acquired or hereditary. Both classically present as a triad of acral dermatitis, diarrhea, and alopecia, though the complete triad is seen in 20% of cases.…”
Section: The Diagnosismentioning
confidence: 99%